Genetic Diversity of Village Chickens in Central Black Sea Region and Commercial Chickens in Turkey by Using Microsatellite Markers - Mercan, L.; OKUMUS, A. (TÜBİTAK erdin@metu.edu.tr, 2015)
Local chicken populations in the Central Black Sea Region of Turkey have been intensively affected by governmental poultry culling due to avian influenza outbreak risks. The aim of this study was to investigate the genetic diversity of indigenous chicken populations raised in the Central Black Sea Region in order to assess genetic structures of these populations and to determine genetic relationships between the study populations and certain commercial chicken genotypes. Genotypic diversity of 45 Turkish village chicken populations located in 5 provinces in the Central Black Sea Region of Turkey and 2 commercial hybrid populations were compared using 28 autosomal microsatellite loci. In total, 363 alleles were observed within 47 populations in 28 microsatellite loci. These loci showed 12.96 ± 4.97 alleles per locus and the mean number of alleles per population was 2.33 ± 0.19. The most polymorphic locus was LEI0234 with 28 alleles and 0.944 polymorphism information content (PIC) value. The least polymorphic locus was LEI0192 with 6 alleles and 0.720 PIC value. The results suggested that despite the extensive culling the studied local chicken populations showed a high genetic diversity compared to commercial hybrid populations. © TÜBI˙TAK.
Keywords: Genetic Diversity; Microsatellite Markers; Village Chickens